Key Success Factors Analysis as a Method of Position Evaluation of the Company (Research Bulletins of the Faculty of Economic Sciences, 2015)
The main aim of this article is to determine the competitive position of the company acting in material and road construction materials based on an analysis of key success factors using a competitive profile. Research questions have been formulated: What are the key success factors in a competitive game company? What is the company's competitive position in relation to its main competitors? This article tends to confirmation that using of competitions analysis and methods is necessary to make an optimal decision in market acting.
Keywords: competitiveness; enterprise; competition; strategic analysis; methods of estimation